ANALISIS TINGKAT BERPIKIR DALAM MENYELESAIKAN SOAL GERAK PARABOLA MENGGUNAKAN TAKSONOMI STRUCTURE OF THE OBSERVED LEARNING OUTCOMES (SOLO) SISWA KELAS X MIA SMAN 1 SUNGAI RAYA - Desi Hartanti; Tomo Djudin; Syukran Mursyid (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2021)
This This study aims to describe the level of students’ thinking profilein solving parabolic motion problems based on the SOLO taxonomy seen from learning outcomes and gender. This is a survey research without a comparison group. Data collection was done by giving 4 questions to 95class X MIA students at SMAN 1 Sungai Raya, and categorized based on learning outcomes (high, medium, low) and gender (male, female). The level ofstudents’ thinking profile in solving parabolic motion problems based on SOLO taxonomyis 50.52% at the pre-structural level, 11.57% at the uni-structural level, 21.05% at the multi-structural level, 16.84% at relational level , and0% at extended-abstract level. Additionally, students with high learning outcomes reached the uni-structural-relational thinking level, while moderate ones reached the uni-structural-multi-structural level, and low ones reached the uni-structural-pre-structural level. In terms of gender,female students' average percentage of thinking level is 44.2% higher than male students with only 33.6% of the ideal score.